Synthesis and Cytotoxic Evaluation of 2-Aryl-7,8-dihydroquinolin-6(5H)-ones - Bautista, Diego Díaz; Blé González, Ever A.; Chávez Santos, Rosa María; Ramírez Apán, María Teresa; Vilchis Reyes, Miguel A.; Martínez, Roberto (Synthesis, 2023)
Herein we present a facile four-step synthetic method for the synthesis of novel 2-aryl-substituted 7,8-dihydroquinolin-6(5H)-ones as cytotoxic agents. The key step was the use of Mannich salts derived from acetophenones as a Michael acceptor in the reaction with cyclohexane-1,4-dione monoethylene acetal to give 1,5-dicarbonyl compounds that were treated with ammonium acetate to give the 7,8-dihydroquinolin-6(5H)-ones. The cytotoxic activity of the synthesized compounds was evaluated against seven cell lines. The observed data showed good selectivity for chronic myeloid leukemia line K-562. The synthetic route was simple and applicable to various functional group containing substrates. These types of compounds may be utilized as lead compounds in cancer research and drug discovery.
Keywords: 7,8-dihydroquinolin-6(5H)-one; cytotoxic test; Mannich salts; leukemia; K-562 cell line